Investigation of the Cases Presenting To Manisa Moris Şinasi Children’s Hospital with a Tick Bite Between 2007 and 2010 - Tonay İnceboz; Mete Demirel; Leyla Över (Güncel Pediatri)
Introduction: The purpose of this study was to investigate the cases with a tick bite in Moris Sinasi Children’s Hospital between January 2007 and December 2010. We aimed to retrospectively determine the types of the tick, distribution of the cases according to months and years and personal characteristics of the cases. Materials and Methods: Total number of cases with tick bite in this period was 433. All withdrawn samples were put into alcohol and glycerine and examined under the light microscope. Demographic characteristics including residential areas of the patients, symptoms related to tick borne diseases of the patients and species and other characteristics of ticks removed from the subjects were investigated. Results: Of all 433 children, 182 (42%) were female and 251 (58%), male. In 285 (65.8%) of 433 tick bite suspected samples, various ectoparasites were detected microscopically. Removed ticks were classified in five genera. The overwhelmingly dominant genera were Hyalomma nymph and it comprised 54% of the collected samples. In terms of ages of children with tick bite suspected samples, 68 (15.7%) were 0-1 year old and accordingly 207 (47.8%) were 2-5 years old, 124 (28.6%) were 6-10 years old and 34 (7.9%) were 11-16 years old. Conclusion: Children are at risk for tick bites and tick-borne diseases, and therefore attention should be given, especially during the summer months. (Journal of Current Pediatrics 2011; 9: 116-21)